2007
DOI: 10.1111/j.1365-2036.2007.03501.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study of five measures of gluten‐free diet adherence in adults with coeliac disease

Abstract: SUMMARY BackgroundIncreasing numbers of individuals are now being diagnosed with coeliac disease. The only accepted treatment for coeliac disease is lifelong adherence to a strict gluten-free diet (GFD). Individuals' ability to adhere to the GFD varies, but systematic studies guiding the assessment of adherence are currently lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 22 publications
5
105
2
5
Order By: Relevance
“…The study recruited a large community sample of people with CD, avoiding the biases associated with recruitment in secondary care or from members of patient societies. shown to correlate to other more objective measures in other studies (Biagi et al 2012, Leffler et al, 20072009). Our data demonstrates that the majority of respondents were able and willing to self-report their adherence in this way and the anonymous nature of the questionnaire may have for facilitated the admission of intentional lapses for some respondents.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The study recruited a large community sample of people with CD, avoiding the biases associated with recruitment in secondary care or from members of patient societies. shown to correlate to other more objective measures in other studies (Biagi et al 2012, Leffler et al, 20072009). Our data demonstrates that the majority of respondents were able and willing to self-report their adherence in this way and the anonymous nature of the questionnaire may have for facilitated the admission of intentional lapses for some respondents.…”
Section: Discussionmentioning
confidence: 65%
“…However, perceived difficulty is associated with the frequency of mistakes made and the confidence in one's ability to stick to the diet (self-efficacy). A lack of a direct association between the reported difficulty of the GFD and adherence has been found by others (Casellas et al, 2006;Leffler et al, 2007). One UK study found, however, that difficulties such as understanding food labelling, affordability, obtaining GF foods and obtaining enough GF foods on prescription were all significantly associated with compliance, but that this was also dependent upon ethnicity (Butterworth, Banfield, Iqbal & Cooper, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Debate exists on the optimal way to measure GFD adherence (Leffler et al, 2007;Ludvigsson et al, 2014;Vahedi et al, 2003), resulting in large variation in definitions and measurement across studies (Hall, Rubin, & Charnock, 2009). Intentional gluten consumption in patients with CD appears rare, with unintentional non-adherence (e.g., due to cross contamination or errors in label reading) representing the most common reason for lapsing from the GFD (Hall, Rubin, & Charnock, 2013;Sainsbury et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used adherence measures, such as single-item self-report questions (e.g., 'how strictly do you adhere to your GFD?' with Likert or visual analogue response scales from 'not at all' to 'very strictly') and serological analyses, are unreliable at detecting incomplete adherence, particularly with increased time on a GFD (Leffler et al, 2007). These methods also do not correlate well with dietitian-rated assessments (Fera, Cascio, Angelini, Martini, & Guidetti, 2003;Leffler et al, 2007;Vahedi et al, 2003), the method currently deemed the 'gold standard' (Leffler et al, 2007;Ludvigsson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation